Stages of Development of Payment Systems : Leapfrogging across Countries and MENA's Place in the World - Gevaudan, Clement; Lederman, Daniel (World Bank, Washington, DC, 2020)
This paper studies the relationship between the level of economic development and the incidence of three forms of payments across countries, namely the incidence of bank accounts, digital payments, and mobile money accounts among the adult populations across countries. It presents simple statistical tests of leapfrogging, the phenomenon by which poor countries surpass rich countries in the provision of payments mechanisms. It contributes to a broader and long-standing literature on stages of development, as well as to the literature on financial development and access to finance. The findings suggest that there is evidence of "absolute" and "relative" leapfrogging, with both terms defined in the paper. In addition, the Middle East and North Africa region, on average, suffers from a notable underperformance gap across all observed stages of payment-systems development. This finding suggests that the region suffers from structural impediments to the development of its financial and banking systems that go well beyond the adoption of digital-technology tools.